THE IMPACT OF THE WITHDRAWAL OF UNITED STATES MILITARY TROOPS ON FOOD SECURITY IN AFGHANISTAN IN 2021-2022 - Izza, Atina; Basuki, Luthfi Wahyu (Universitas Nasional, 2024)
This study analyzes the impact of the United States' armed military invasion of Afghanistan, initiated after the 9/11 tragedy, on food security in Afghanistan during the years 2021-2022. The research employs a qualitative approach, interpreting data through a descriptive method using literature review from articles, journals, and related scientific studies. The theoretical framework integrates Hegemony Theory to examine U.S. power in Afghanistan and Food Security Theory to assess the food security situation in Afghanistan during 2021-2022. The U.S. military invasion in Afghanistan resulted in economic, food, and political instability, placing the country under significant food security threats, exacerbated by geographic challenges that hinder economic recovery. After the full military withdrawal by the U.S. in 2021, driven by a shift in foreign policy prioritizing diplomacy, alongside critiques of the U.S. occupation and the